If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 2k + 3 = -3 Reorder the terms: -2 + 3 + 2k = -3 Combine like terms: -2 + 3 = 1 1 + 2k = -3 Solving 1 + 2k = -3 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2k = -3 + -1 Combine like terms: 1 + -1 = 0 0 + 2k = -3 + -1 2k = -3 + -1 Combine like terms: -3 + -1 = -4 2k = -4 Divide each side by '2'. k = -2 Simplifying k = -2
| 4x+28=2x | | 8-3x+7x=15-3x | | 0.125y+0.1(800-y)=85 | | X+1+3=4 | | 2.7(-16)+2.2=2.4(-16)-2.6 | | 3(1)+6= | | 0.05+0.09(3x)=32 | | 6.5y-3=5.5y+1 | | x+(.05x)=49.77 | | -v-2v=-9 | | 6.5y-3=5.5+1 | | 4(g+2)+3=19 | | 42x-7=9-4 | | 4(x+2)=21(x-3) | | 3-v=1 | | 1-3n-2n=-4 | | 1-v-3=0 | | 2.7x+2.2=2.4x-2.6 | | 1-v-3=I | | (3+v)(4v+1)=0 | | 10x+3=3+12x | | 20-6x=34 | | 1-z=7.2 | | 9x^2+11x+9=0 | | 2xsquared=6x | | -5x+9=-71 | | 6n=17+7 | | 3x-8+x=2(2x-4) | | 3x+12x-7x= | | 3y+2x=72 | | 5x+2y=92 | | 10x+5=7x+4 |